2020
DOI: 10.1038/s41598-020-61816-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-670 modulates Igf2bp1 expression to regulate RNA methylation in parthenogenetic mouse embryonic development

Abstract: Aberrant epigenetic modification, including N6-methylation of adenosine (m6A), has been frequently reported in embryos derived from parthenogenetic activation (PA). However, the role of Igf2bp1 expression pattern in m6A modification and the mechanism through which Igf2bp1 function is regulated in PA embryos remains elusive. Therefore, in this study, using si-Igf2bp1 and betaine (N,N,N-trimethylglycine, a major methyl donor), we investigated the effect of Igf2bp1 expression in m6A modification on the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…In contrast to YTHDF2, which functions in the promotion of mRNA decay, recent studies revealed that IGF2BPs could act as a new class of cytoplasmic m 6 A readers that promote the stability and storage of mRNAs (Huang et al, 2018). It was reported that IGF2BP1 deletion suppressed the RNA m 6 A modification level in mouse embryos and caused impaired early parthenogenetic (PA) embryogenesis, whereas supplementation with betaine increased the RNA m 6 A modification level and rescued embryonic development (Hao et al, 2020). In addition, miR-670-3p was found to regulate IGF2BP1 and affect apoptosis in PA embryos (Hao et al, 2020).…”
Section: The Influences Of M 6 a On Preimplantation Embryo Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to YTHDF2, which functions in the promotion of mRNA decay, recent studies revealed that IGF2BPs could act as a new class of cytoplasmic m 6 A readers that promote the stability and storage of mRNAs (Huang et al, 2018). It was reported that IGF2BP1 deletion suppressed the RNA m 6 A modification level in mouse embryos and caused impaired early parthenogenetic (PA) embryogenesis, whereas supplementation with betaine increased the RNA m 6 A modification level and rescued embryonic development (Hao et al, 2020). In addition, miR-670-3p was found to regulate IGF2BP1 and affect apoptosis in PA embryos (Hao et al, 2020).…”
Section: The Influences Of M 6 a On Preimplantation Embryo Developmentmentioning
confidence: 99%
“…It was reported that IGF2BP1 deletion suppressed the RNA m 6 A modification level in mouse embryos and caused impaired early parthenogenetic (PA) embryogenesis, whereas supplementation with betaine increased the RNA m 6 A modification level and rescued embryonic development ( Hao et al, 2020 ). In addition, miR-670-3p was found to regulate IGF2BP1 and affect apoptosis in PA embryos ( Hao et al, 2020 ). Subsequently, Liu H.B.…”
Section: A Modification and Mammalian Embryonimentioning
confidence: 99%
“…mRNA stability was also regulated by m6A. The m6A reader IGF2BP1 and YTHDF2 have been reported to regulate the early embryo development [9,10,29], while the m6A methyltransferase METTL3 was essential for fertility [30]. The down-regulation of METTL3, IGF2BP1, and YTHDF2 might impede the early embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA stability was also regulated by m6A. The m6A reader IGF2BP1 and YTHDF2 have been reported to regulate the early embryo development [ 9 , 10 , 30 ], while the m6A methyltransferase METTL3 was essential for fertility [ 31 ]. The down-regulation of METTL3 , IGF2BP1 , and YTHDF2 might impede the early embryo development.…”
Section: Discussionmentioning
confidence: 99%